IL‐6 receptor antagonist as adjunctive therapy with clotting factor replacement to protect against bleeding‐induced arthropathy in hemophilia. Issue 5 (15th May 2013) - Narkbunnam, N.; Sun, J.; Hu, G.; Lin, F.‐C.; Bateman, T. A.; Mihara, M.; Monahan, P. E.
Summary Background The most common morbidity that results from hemophilia is bleeding‐induced hemophilic arthropathy (HA), which once established may not be interrupted completely even by prophylactic clotting factor replacement. Specific therapies to oppose inflammatory cytokines, including Interleukin 6 (IL‐6) receptor antagonists, have become important in the management of inflammatory arthritides. Objectives We investigated combining therapy using MR16‐1, a rat IgG antibody directed against mouse IL‐6 receptor (anti‐IL‐6R), with factor VIII (FVIII) replacement to protect against bleeding‐induced arthropathy in hemophilia A mice. Methods Three recurrent hemarthroses were induced in the knee joint capsule of FVIII knockout mice. Treatment at the time of each hemorrhage included either: no treatment; FVIII replacement given at the time of hemorrhage; FVIII replacement at hemorrhage plus anti‐IL‐6R as 4‐weekly injections; FVIII replacement with non‐specific control antibody (rat IgG); and anti‐IL‐6R alone without FVIII replacement. Six weeks following the first hemarthosis, joints were harvested and histopathology was scored for synovitis, for cartilage integrity and for macrophage infiltration. Results Animals that received anti‐IL‐6R as an adjunct to FVIII replacement demonstrated the best survival and the least acute joint swelling and pathology on histologic examination of the synovium and cartilage (P < 0.05 for each parameter). All histopathologic parameters in the mice receiving FVIII+anti‐IL‐6R were limited and were comparable to findings in injured hemostatically normal mice. The major benefits of adjunctive anti‐IL‐6R were decreasing synovial hyperplasia, hemosiderin deposition and macrophage infiltration. Conclusions Short‐course specific inhibition of inflammatory cytokines as an adjunct to replacement hemostasis may be an approach to minimize hemophilic joint degeneration.